1936
DOI: 10.1084/jem.63.6.819
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Studies on the Precipitin Reaction

Abstract: In the studies on the precipitin reaction hitherto published from this laboratory (1) the salt concentration was held constant at 0.9 per cent of sodium chloride in order to permit observations on the effect of varying the proportions of antigen (or hapten) and antibody. In the present paper are reported data obtained during several years on the influence on the course of the precipitin reaction of changes in the concentration of sodium chloride and on the effect of other cations and anions.According to our qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

1945
1945
1983
1983

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 5 publications
4
15
0
Order By: Relevance
“…This behavior is analogous, in part, to that observed by Heidelberger, Kendall, and Teorell (36), for the influence of high concentrations of NaCI on the reaction of SIII with the homologous antibody, although there, in contrast to the present data, the general course of the reaction was not altered. In neither instance was the effect of salts directed toward an increased solubility of the precipitate since no additional precipitation occurred upon dialysis unless more antigen was added.…”
Section: 4-supporting
confidence: 89%
See 1 more Smart Citation
“…This behavior is analogous, in part, to that observed by Heidelberger, Kendall, and Teorell (36), for the influence of high concentrations of NaCI on the reaction of SIII with the homologous antibody, although there, in contrast to the present data, the general course of the reaction was not altered. In neither instance was the effect of salts directed toward an increased solubility of the precipitate since no additional precipitation occurred upon dialysis unless more antigen was added.…”
Section: 4-supporting
confidence: 89%
“…have suggested that competition of the cation with the antibody for combination with the acidic groups of the polysaccharide is responsible for the inhibitory effect of concentrated NaC1 (36). Undoubtedly this does not apply to the present phenomenon since it is an anionic effect, and hence it can hardly be explained in terms of an electrostatic shielding of these groups.…”
Section: 4-mentioning
confidence: 70%
“…of the mixture per injection as above. If not immediately used, the antisera obtained from these rabbits were frozen and stored at -18 0 C. The titer of the antisera was obtained by measuring the total protein content of the precipitate, 48 or by a radioisotopic technic, 49 using I-125 labeled guinea pig y, | S and a globulins. 50 For the insulin antibody assay radioactive insulin was diluted with a 1 per cent bovine serum albumin in borate buffer (^H 8.5, 0.13M) and with carrier crystalline beef insulin; the final concentration of insulin-I-125 w a s 3-8 uc.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Heidelberg et al [22] noted that increasing NaCl concentration above 0.15 M would reduce the complexing of antibody with antigen. The gel filtration procedure was therefore repeated, but the proteins were eluted from the column with 0.7 M NaCl in 0.001 M phosphate buffer, pH 7.…”
Section: Fraction Numbermentioning
confidence: 99%